182k views
1 vote
From the sum of 3x-4y+5z,2x-7y and 9z-5y subtract -2xy-2y-2z

User Kenske
by
6.1k points

1 Answer

1 vote

Answer:

5x - 14y + 16z + 2xy

Explanation:

Given expressions:

3x - 4y + 5z

2x - 7y

9z - 5y

-2xy - 2y -2z

Solution:

Sum of 3x - 4y + 5z

2x - 7y

9z - 5y

= 3x - 4y + 5z + 2x - 7y + 9z - 5y

= 3x + 2x - 4y - 7y -5y + 5z + 9z

= 5x - 16y + 14z

Subtract -2xy - 2y -2z

= 5x - 16y + 14z - ( -2xy - 2y -2z )

= 5x - 16y + 14z + 2xy + 2y + 2z

= 5x - 16y + 2y + 14z + 2z + 2xy

= 5x - 14y + 16z + 2xy

User NVitius
by
6.0k points